Evidence for nucleation-growth, redistribution, and dissolution mechanisms during the course of redox cycling experiments on the C-60/NBu4C60 solid-state redox system: Voltammetric, SEM, and in situ AFM studies - Suarez, M; Marken, F; Compton, R; Bond, A; Miao, W; Raston, C (1999)
The electrochemical reduction of solid C60 abrasively attached in the form of microcrystals to graphite and glassy carbon electrode surfaces and then immersed in acetonitrile containing 0.1 M NBu4PF6 or NBu4ClO4 as the electrolyte has been studied. Voltammetric responses observed after the initial stages of redox cycling experiments, when redistribution processes occur, are consistent with those observed previously for so-called "film" deposits. The characteristic "steady-state" shape of the solid-state voltammetric response with a large potential gap between reduction and reoxidation responses is shown by chronoamperometric experiments to be associated with the presence of a nucleation and growth-type mechanism. The initial three reduction processes of C60 attached to the electrode surface, which lead to the chemically reversible formation of only slightly soluble C60- and C602- and finally to the loss of the soluble C603- have been followed by ex situ SEM and in situ AFM experiments. The extent of the electrochemical conversion is shown to depend strongly on the crystal size, with larger crystals being affected only at the solid - liquid interfacial region. Evidence for stochastic processes further supports the proposed nucleation and growth-type mechanism. Crystal redistribution processes also are identified by the AFM measurements.